PENGEMBANGAN MEDIA VIDEO ANIMASI BERBASIS STRATEGI PAIKEM PADA MATA PELAJARAN BAHASA INDONESIA UNTUK MENDUKUNG MERDEKA BELAJAR SISWA KELAS IV SEKOLAH DASR - Apreasta, Lika; Mahmudi, Moh. Rosyid; Wati, Siti Novia (Jurnal Tunas Pendidikan, 2023)
The background of this writing is the inaccurate selection of paikem strategy-based video animation media in Indonesian subjects to support the independence of grade IV elementary school students. Inappropriate learning media cannot fully accommodate students' learning styles. This writing aims to produce a product in the form of valid, practical, and effective animated video media for reading fable texts and writing nominal money in class IV. This type of research is development research. This study uses a 4D development model. The test subjects in this study were fourth grade students at SDN 82/VI Rantau Limau Kapas and fourth grade Indonesian language teachers.The research conducted shows that the video animation media based on the Paikem strategy developed is valid, practical and effective. So it can be concluded that from the process of developing animated video media based on the Paikem strategy in learning to read fable texts and write nominal class IV money, it has produced media that is (1) valid, both in terms of aspects as media, language aspects, and material aspects, (2) media that is practically used from both the student and teacher aspects, and (3) has produced effective media to achieve learning objectives according to the curriculum